2022
DOI: 10.3389/fpubh.2022.982159
|View full text |Cite
|
Sign up to set email alerts
|

Tax competition, environmental regulation and high-quality economic development: An empirical test based on spatial Durbin model

Abstract: Studying economic development in China is a very important topic recently because China's economy is moving toward high-quality development and local governments face the dilemma of environmental governance and economic development. To contribute to the literature in this area further, this paper assesses the impact of tax competition and environmental regulation on high-quality economic development through the spatial Durbin model and instrumental variable and by using the data from 278 prefecture-level and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Zhang et al [ 62 ] found that environmental regulations have different effects on GTI in China’s resource-based and non-resource-based cities. Shangguan et al [ 63 , 64 ] found that there is heterogeneity in the impact of environmental regulation on air pollution and high-quality economic development in large, medium, and small cities. It can be seen that the urban heterogeneity of the impact of environmental regulation is widespread.…”
Section: Discussion and Policy Implicationsmentioning
confidence: 99%
“…Zhang et al [ 62 ] found that environmental regulations have different effects on GTI in China’s resource-based and non-resource-based cities. Shangguan et al [ 63 , 64 ] found that there is heterogeneity in the impact of environmental regulation on air pollution and high-quality economic development in large, medium, and small cities. It can be seen that the urban heterogeneity of the impact of environmental regulation is widespread.…”
Section: Discussion and Policy Implicationsmentioning
confidence: 99%
“…However, under a hierarchical administrative system in which the central government has authority, local officials who want to be promoted must work on the basis of the central government's preferences. Therefore, local governments will devote more administrative resources to measures that promote economic growth and disregard the regulation of environmental degradation when the central government sets a high priority on GDP targets [ 48 ]. Of course, the preferences of the central government are not static.…”
Section: Theoretical Analysismentioning
confidence: 99%
“…At the same time, with the advent of the era of digital economy, the traditional forms of production organization have undergone drastic changes. The new elements of value creation have changed the way of cross-border transactions among countries, prompted the world economy to complete the transformation of old and new kinetic energy, and aggravated the imbalance of economic development among countries and the dilemma of the invalidation of traditional international tax rules (Appiah-Kubi et al, 2021;Shangguan et al, 2022;Ding et al, 2022). Specifically, with the deepening of multilateral cooperation and the successive implementation of BEPS action plans in various countries, the international tax governance order has entered the "post-BEPS era".…”
Section: The Traditional Tax Governance Order Is Facing the Dilemma O...mentioning
confidence: 99%